2003
DOI: 10.1590/s1519-566x2003000400014
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis survey in Brazil: geographical distribution and insecticidal activity against Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae)

Abstract: Levantamento de Bacillus thuringiensis no Brasil: Distribuição Geográfica e Atividade Inseticida ContraSpodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae)RESUMO -O total de 3408 cepas de Bacillus thuringiensis foi isolado de 1448 amostras de solo provenientes de 10 estados, em quatro regiões brasileiras, abrangendo 96 municípios. As cepas foram avaliadas contra lagartas de Spodoptera frugiperda (J. E. Smith) sendo que apenas 62% mataram entre 81% e 100%, e 1758 não causaram mortalidade. O Sul destacou-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 11 publications
3
28
0
Order By: Relevance
“…In all of the soil samples that were collected in this study, bacterial growth was detected with an average of 2.53 B. thuringiensis isolates/sample, which corresponds with the averages of 3.45, 2.35 and 1.91 B. thuringiensis isolates/ sample that were previously described by Polanczyk et al (2003), Valicente and Barreto (2003), and Barreto (2005), respectively. Because the isolates were initially characterized from the soil samples by morphological features, we sequenced the 16S ribosomal subunit genes of the isolates to confirm that they were B. thuringiensis.…”
Section: Discussionsupporting
confidence: 84%
“…In all of the soil samples that were collected in this study, bacterial growth was detected with an average of 2.53 B. thuringiensis isolates/sample, which corresponds with the averages of 3.45, 2.35 and 1.91 B. thuringiensis isolates/ sample that were previously described by Polanczyk et al (2003), Valicente and Barreto (2003), and Barreto (2005), respectively. Because the isolates were initially characterized from the soil samples by morphological features, we sequenced the 16S ribosomal subunit genes of the isolates to confirm that they were B. thuringiensis.…”
Section: Discussionsupporting
confidence: 84%
“…B. thuringiensis can be found in different substrates such as soil, water, plant surfaces, dead insects, grain dust, spider webs and stored grain (Glare & O’Callaghan 2000; Valicente & Barreto 2003; and Miralles & Peres 2004). This bacterium also shows a high genetic variability and is widely distributed in nature (Vilas-Boas et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The isolates containing cyt genes identified in this study showed different levels of toxicity against S. frugiperda (Valicente et al, 2000;Valicente & Barreto, 2003;Valicente & Fonseca, 2004;Valicente et al, 2010). Two isolates caused 100% mortality (isolates 1646JAB and 1656JAB) and one caused 79% of larval mortality (strain 1168C).…”
Section: Screening Of Cyt Genes In Bt Collectionmentioning
confidence: 78%
“…These isolates expressed different toxicities against S. frugiperda larvae (Valicente & Barreto, 2003). In addition, Bt var.…”
Section: Bacterial Strainsmentioning
confidence: 99%